MIDDLE EAST RESPIRATORY SYNDROME CORONA VIRUS ALERT VERIFICATION IN MIRPUR, AZAD KASHMIR - Khan, Mumtaz Ali; Ishaq, Muhammad; Rehman, Mujeeb Ur; Altaf, Asim; Baig, Mirza Aamir; Rana, Safdar; Kamran, Jaleel; Ranjha, Muazam Abbas; Rana, Jawad Asgher (Journal of Ayub Medical College Abbottabad, 2017)
Background: Middle East Respiratory-Corona virus (MERS-CoV), SARS like virus, identified in September 2012 in Middle-East. February 2013, an elderly man, who visited Pakistan and KSA, was confirmed as MRS-CoV in UK. A team visited Mirpur to assess current and past SARI trends in major indoor facilities, to explore possible contact of the patient with known or suspected SARI case during his stay in Pakistan and enlist close contacts. Methods: Review of indoor records in hospitals, interviews with relatives & physicians and active contact tracing using operational case definition. Results: Arrived on 16th December 2012, mostly stayed at daughter’s house, visited by relatives, on 19th January, left for KSA accompanied by daughter, developed fever with chills and body aches on 23rd January. On 28th January, arrived London, admitted at City Hospital, Birmingham, subsequently shifted to Manchester Hospital on 6th February 2013, diagnosed as MERS-CoV, expired on 19th February. His son having underlying condition, confirmed as MERS-CoV on 13th February, and expired on 17th February. Daughter developed mild respiratory symptoms, confirmed as MERS-CoV on 16th Feb and recovered. Both have been infected by the Index case. The review of indoor record did not reveal any significant change in SARI trends, the cumulative number of cases for the January -February 2012 and 2013 was 291 and 294 respectively indicating no difference. During his stay in Pakistan, he didn’t meet any suspected/ill person. Close contacts were observed and investigated for MERS-CoV, all remained healthy. Conclusions: The available evidence does not suggest any MERS-CoV transmission to, or from the patient in Pakistan. Keywords: MERS-CoV; Transmission.